Maximum Power Point Tracker Using Fuzzy Logic Controller with Reduced Rules - Adel Haddouche; Mohammed Kara; Lotfi Farah (Institute of Advanced Engineering and Science, 2018)
This paper presents a fuzzy logic controller for maximum power point tracking (MPPT) in photovoltaic system with reduced number of rules instead of conventional 25 rules to make the system lighter which will improve the tracking speed and reduce the static error, engendering a global performance improvements. in this work the proposed system use the power variation and current variation as inputs to simplify the calculation, the introduced controller is connected to a conventional grid and simulated with MATLAB/SIMULINK. The simulation results shows a promising indication to adopt the introduced controller as an a good alternative to traditional MPPT system for further practical applications